Expected responses to aggregate trait selection in maize (Zea mays L.) - Ajala, S. (2010)
This study was conducted with the objective of predicting and comparing expected gains for two selection indices and to aid identification of a better index to improve maize populations for a target environment, in thiscase, small-farm conditions. Data from S2 lines from each of three populations evaluated at three locations in 1988 were subjected to (a) an index that uses economic weights and (b) rank summation index (RSI) that is both weight and parameter free. Responses to single trait selections were much higher than using an index. RSI was considered a better index because it was operationally more efficient and simpler. Selection through RSI will in addition to improving the aggregate trait in the desired direction, improve grain yield and will not increase height much.